Simultaneous determination of refractive index and thickness of multilayer dielectric films by discrete Fourier transform - Köysal, O; San, SE; Özder, S (Elsevier Science Bv, 2004)
In this work a novel method is proposed for simultaneous determination of refractive index n and geometrical thickness d. Transmittance spectra of dielectric films, exhibiting weakly absorbance in 14,285-14,492 cm(-1) region, were exposed to Discrete Fourier Transform (DFT) whereby {n, d} values were extracted at the same time. Refractive index variation of films is assumed to be constant in the measurement range. Obtained results revealed favourable accordance with the literature and mechanical micrometer readings. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: transmittance; Discrete Fourier Transform; thin film; thickness; refractive index